2021
DOI: 10.1186/s12937-021-00666-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining weight loss among adults with obesity using a digital meal planning and food purchasing platform for 12, 24, and 36 months: a longitudinal study

Abstract: Background Previous studies have shown that lifestyle changes, such as diet and exercise, can lead to weight loss, resulting in dramatic improvements in overall health and chronic disease risk. However, while many traditional dieting, food tracking and weight loss coaching programs result in short-term weight loss, there is less evidence of their effectiveness on sustaining weight loss over time. Methods We conducted a retrospective analysis of 1,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, to date, only four studies [ 14 , 15 , 16 , 17 ] have analyzed the effectiveness of such treatments in patients with both health conditions—that is, in individuals presenting an OB-HTN phenotype. Of note, none of the four studies performed in this specific area, and only one in non-hypertensive obese adults [ 18 ], followed up with patients who had completed an online educational intervention for at least 3 years. In addition, to the best of our knowledge, no research has yet analyzed the effects of a second intervention (reintervention) with an online intervention program in patients with OB, HTN, or any other type of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, only four studies [ 14 , 15 , 16 , 17 ] have analyzed the effectiveness of such treatments in patients with both health conditions—that is, in individuals presenting an OB-HTN phenotype. Of note, none of the four studies performed in this specific area, and only one in non-hypertensive obese adults [ 18 ], followed up with patients who had completed an online educational intervention for at least 3 years. In addition, to the best of our knowledge, no research has yet analyzed the effects of a second intervention (reintervention) with an online intervention program in patients with OB, HTN, or any other type of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…An app-based approach would offer additional capabilities, such as structured monitoring of compliance and health outcomes, the opportunity to provide feedback [ 58 ], enhanced portability and would potentially facilitate more extensive customisation of the planner. The use of digital approaches to diet behaviour change, such as the use of a digital planning and purchasing platform [ 59 ] and digital weight management interventions, with one-to-one health coaching [ 12 ], have resulted in sustainable weight loss in obese populations. A systematic review in 2019 concluded that “app-based mobile interventions are effective and highly promising for changing nutrition behaviours and nutrition-related health outcomes” [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foodsmart uses a multipronged approach including educating individuals on how to eat healthy, leveraging the food frequency questionnaire, recommending personalized healthy recipes based on food preferences, and automating grocery list creation and online grocery purchasing, all while tracking the individual’s improvements in biometrics. The platform has been found to be associated with at least 5% weight loss and has been shown to sustain weight loss over 3 years [ 11 , 12 ]. Previous research has suggested that by simply cooking at home rather than ordering food or eating out, diet quality improves [ 13 ].…”
Section: Introductionmentioning
confidence: 99%